Ngevape: Peralihan, Etika, dan Penolakan Penggunaan Vape di Kalangan Mahasiswa - Adi Jahyadi Adi Jahyadi (Universitas Muslim Maros, 2023)
Smoking is one of the important complements in the daily life of a smoker. Currently, electric cigarettes (vape) are becoming more popular and trendy than conventional cigarettes. While existing literature looks at the effects, lifestyle, Islamic views on vaping, little (if any) literature focuses on the ethics and social disapproval of vaping, this article fills in this gap. It examines why college students switch from conventional cigarettes to vape, the ethics and rejection of vape use around others. Using qualitative approach, this study was carried out at Hasanuddin University. Those who participated in this study were 11 students whose age ranging between 19 and 22 years old and who use or consume electric cigarettes. Observation and in-depth interview were combined as data collection methods. Many students who used to smoke conventional cigarettes now become vape users. There are various reasons why students switch from conventional cigarettes to vape, namely: environmental influences, unique vape aroma, cheaper, simpler, harmless, trendy and more stylish. Apart from this, vape users also have ethics that they must adhere to when consuming vape because not everyone is permissive about using vape around them. Vape users often encounter obstacles when vaping, such as direct warnings and gestures’ warning. It is argued in this article that despite the fact that vaping use is still controversial, it has become more socially acceptable than it used to be, and applying the ethics and becoming sensible to others has contributed to such acceptability.